LEXICAL RELATIONS IN BILLIE EILISH'S 'HAPPIER THAN EVER' ALBUM LYRICS - Kurniawan, Dandy; Purnama Sari, Dewi (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
This article examines the lexical relations present in the lyrics of Billie Eilish's album Happier Than Ever. Using Saeed's theory of lexical relations, the study explores various meaning relations, including synonymy, antonymy, polysemy, hyponymy, meronymy, and member collection, as they appear in the album's lyrics. The research adopts a descriptive analysis approach, analyzing the lyrics of all 16 songs in the album to identify and categorize instances of lexical relations. Each song was examined in detail to explore how lexical choices contribute to the overarching themes and emotions conveyed in the album. The analysis revealed 16 instances of polysemy, 13 of antonymy, 12 of synonymy, 5 of hyponymy, 2 of meronymy, and 1 instance of member collection. Polysemy was found to be the most dominant lexical relation, highlighting the complexity and layered meanings in Eilish's lyrics. The findings suggest that the strategic use of lexical relations enhances the thematic depth and emotional resonance of the Happier Than Ever album, reflecting themes of mental health, personal struggle, and societal pressures. This study demonstrates that lexical semantics in contemporary music can serve as a powerful tool for conveying nuanced emotional narratives, contributing to the broader field of linguistic studies in music.